A tale of migrations from east to west: the Irano‐Turanian floristic region as a source of Mediterranean xerophytes. (8th August 2013) - Manafzadeh, Sara; Salvo, Gabriele; Conti, Elena; Ebach, Malte
Abstract Aim The Irano‐Turanian (IT) floristic region is characterized by high levels of endemicity. Despite its potential role as a cradle of xerophytic taxa for neighbouring areas, its biogeographical history remains poorly studied. Haplophyllum, a diagnostic element of the IT region, was used as a model to discriminate between alternative biogeographical scenarios for the evolution of the region and, more specifically, to investigate whether it served as a source of xerophytes for the colonization of the Mediterranean Basin. Location Irano‐Turanian floristic region (Central Asia and West Asiatic areas) and Mediterranean floristic region (western and eastern parts of the Mediterranean Basin). Methods Three chloroplast DNA regions were sequenced in 77 accessions of Haplophyllum and 37 accessions from other subfamilies of Rutaceae. To elucidate the temporal and spatial evolution of Haplophyllum in the IT and Mediterranean regions, we performed Bayesian molecular dating analyses with four fossil constraints and ancestral range reconstructions, respectively. Results Our molecular dating and ancestral area reconstruction analyses suggest that Haplophyllum originated in the Central Asian part of the IT region during the early Eocene and started to diversify in situ during the early Oligocene, soon after the vanishing of the Tethys Ocean. Our results further imply that Haplophyllum later invaded the eastern Mediterranean Basin in the middle‐to‐late Miocene, concomitantly with the Paratethys Salinity Crisis and rapid palaeobiogeographical changes in the proto‐Mediterranean. Finally, Haplophyllum diversified in the western Mediterranean in the early Pliocene at the end of the Messinian Salinity Crisis. Main conclusions The IT floristic region can serve as a 'donor' of xerophytic taxa to 'recipient' neighbouring regions, including the Mediterranean floristic region. The climatic/geological processes during the Miocene–Pliocene, by increasing aridity and topographic heterogeneity, facilitated range shifts and allopatric speciation in the region.